Cobalt-based co-ordination complex-derived nanostructure for efficient oxygen evolution reaction in acidic and alkaline medium. Issue 10 (October 2022) - Kumar, Naveen; Sharma, Aashima; Rajput, Kritika; Kataria, Ramesh; Mehta, S.K.
Abstract: Electrochemical water splitting is one of the most important method for energy conversion and storage. For this, the design and development of a low-cost robust electrocatalyst are highly desirable. In this study, Cobalt-based electrocatalyst for Oxygen Evolution Reaction was synthesized by thermal treatment of Cobalt-dehydroacetic acid (Co-DHA). The as-synthesized Co nanostructures and Co-DHA crystals were characterized with powder X-ray diffraction, X-ray photoelectron spectroscopy thermo-gravimetric analysis, and field emission scanning electron microscopy. The electrochemical O2 evolution study shows the overpotential (at 10 mV/cm −2 ) correspond to 294 mV vs reference hydrogen electrode (RHE) for K-300 (Co3 O4 @300), whereas K-500 (Co3 O4 @500) shows 170 mV vs RHE values in 1 M KOH solution, respectively. Similar trends have been observed for electrochemical O2 evolution studies in 0.5 M H2 SO4, where K-300 and K-500 shows the overpotential (at 10mV/cm −2 ) of 234 mV vs RHE, and 199 mV vs RHE, respectively. The outcomes show better catalytic efficiency of K-500 as compared to K-300. Graphical abstract: Image 1 Highlights: Simple one pot synthesis for precursor of Co3 O4 . Enhanced activity for oxygen evolution reaction. Efficient performance and stability in both acidic and alkaline medium. Abstract : Cobalt nanostructures; Dehydroacetic acid; Cobalt oxide; O2 evolution; Electrocatalyst.